PENGARUH ONLINE CONSUMER REVIEW DAN ONLINE CONSUMER RATING TERHADAP ONLINE PURCHASE DECISION PRODUK WARDAH OFFICIAL SHOP MARKETPLACE SHOPEE (STUDI KASUS PADA MAHASISWI MANAJEMEN UMB) - Wulandari, Amelia; Bahrun, Khairul (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This study aims to determine the influence of online consumer reviews and online consumer ratings on online purchase decisions of Wardah Official Shop products on the Shopee marketplace (case study on management students of UMB). This research is quantitative. The population in this study consists of 400 management students at UMB who use Wardah products. The object of this research is 180 management students at UMB who are consumers of Wardah products on the Shopee marketplace. In this study, the author used data collection methods through observation, interviews, and the distribution of questionnaires. The data analysis techniques used in this research include instrument tests, classical assumption tests, respondent response analysis, multiple linear regression analysis, hypothesis testing, and determination coefficient analysis (R2). The results of this study indicate that online consumer reviews and online consumer ratings have a positive and significant effect on online purchase decisions. Keywords : Online Consumer Review, Online Consumer Rating, Online Purchase Decision.